2012
DOI: 10.1080/17450128.2011.651172
|View full text |Cite
|
Sign up to set email alerts
|

Migration status and self-reported health among high school students in Stockholm: A cross-sectional study

Abstract: This article aims to determine the self-reported health status of Swedish high school students with respect to gender and immigrant background. The sample was randomly selected from high school students aged 15-19, and 446 students participated in this study. The Nottingham Health Profile (NHP) was used for capturing health status. The results showed that the most common problem was related to energy level (23%) and the least to physical mobility (1%). The proportion for other domains ranged from 2% to 14%. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
(74 reference statements)
2
5
0
Order By: Relevance
“…As mentioned earlier, this study is part of larger project about health and social alienation. The higher self-reported health problem among females than among males is in agreement with the finding of the substudy about health and immigration background of Swedish adolescents (Safipour et al, 2012). Most of the literature indicates that regardless of the country of origin, females generally report more health problems than males and the level of health problems is higher among immigrant females (Ådnanes, 2007;Hall-Lande et al, 2007;Killeen, 1998;Newman & Newman, 2001).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…As mentioned earlier, this study is part of larger project about health and social alienation. The higher self-reported health problem among females than among males is in agreement with the finding of the substudy about health and immigration background of Swedish adolescents (Safipour et al, 2012). Most of the literature indicates that regardless of the country of origin, females generally report more health problems than males and the level of health problems is higher among immigrant females (Ådnanes, 2007;Hall-Lande et al, 2007;Killeen, 1998;Newman & Newman, 2001).…”
Section: Discussionsupporting
confidence: 63%
“…Results from previous studies indicate that a feeling of alienation is higher among Swedish adolescents with an immigrant background (Safipour, Schopflocher, Higginbottom, & Emami, 2011a). The results also revealed that poor selfreported health is higher among females than among males and also higher among students with immigrant background than among the native Swedes (Safipour, Higginbottom, Tessma, & Emami, 2012). Alienation was also identified as a mediating factor between mental and physical health (Safipour, Schopflocher, Higginbottom, & Emami, 2011b).…”
Section: Introductionmentioning
confidence: 68%
“…This is in line with the World Health Organization (WHO) who lists health equity as one of the goals of health promotion (WHO, 1986). According to research and governmental reports, young people in Sweden aged 16–24 have had worse health developments than other age groups in recent decades (Hagquist, 2010, 2011; National Board of Health, 2009; Safipour, Higginbottomb, Mesfin, & Emamid, 2012). For example, mental health issues and problems have increased among older adolescents (Hagquist, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Deprivation and all other hazards (see e.g., Krieger’s theory above—[ 13 , 16 ]) may constitute risk factors contributing to poorer health of immigrants. As for research results on health of migrants, many studies have reached the conclusion that most migrants are disadvantaged as compared to the majority of the population, even after controlling for age, gender, and socioeconomic factors (see e.g., in [ 10 , 23 , 29 , 30 , 31 ]). Nevertheless, some other results of research activities may not identify the same significant differences (e.g., [ 32 ]).…”
Section: Introductionmentioning
confidence: 99%
“…When summarizing research activities in the field of “discrimination and health” with special regard to immigrants or diverse domestic population groups, most of the studies to date were published in the US (mostly looking at African Americans, Latinos or other immigrant groups), be it conceptual [ 13 , 16 ], methodological/methodical [ 41 ] or “summarizing meta-reports” (like e.g., [ 6 , 7 ] or [ 8 ] or other various studies—see e.g., [ 9 , 11 , 12 , 42 , 43 , 44 , 45 , 46 , 47 ]). Nevertheless, some empirical studies have also been done in Western, Northern and Southern Europe—e.g., [ 5 , 19 , 28 , 31 , 37 , 48 ]. We have, however, found no similar study in Central/Eastern Europe, where research into these issues, particularly in post-communist countries, is very underdeveloped.…”
Section: Introductionmentioning
confidence: 99%